2018
DOI: 10.1080/09546553.2018.1481050
|View full text |Cite
|
Sign up to set email alerts
|

Lone Actor Terrorists: A Residence-to-Crime Approach

Abstract: Environmental criminology is concerned with understanding the role of settings and geography more broadly in crime, as well as other related, proximal determinants of criminal activity with an emphasis on the role of person-situation interactions. 1 The approach has been very influential in shaping thinking and practice in crime prevention over the last forty years, growing hand in hand with the evidence-based policing movement. Insights from environmental criminology are increasingly prevalent within the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Bouhana, et al () report the striking similarity between extreme right wing terrorists and other ideologically driven lone actor terrorists in their background and preparatory behaviors, confirming an operational premise and finding within the TRAP‐18 that it generalizes across ideologies (Meloy & Gill, ). Further, Marchment, et al () studied the geographical hunting patterns of lone actor terrorists and found them to engage in spatial decision‐making similar to other criminals. Terrorist violence risk assessment, however, is not necessarily improved by the addition to an instrument of more and more variables arguably associated with such violence (Pressman & Flockton, ); a more parsimonious instrument, on the other hand, may be both scientifically reliable and more practically useful for counterterrorism efforts to prevent such acts of targeted violence.…”
Section: Discussionmentioning
confidence: 99%
“…Bouhana, et al () report the striking similarity between extreme right wing terrorists and other ideologically driven lone actor terrorists in their background and preparatory behaviors, confirming an operational premise and finding within the TRAP‐18 that it generalizes across ideologies (Meloy & Gill, ). Further, Marchment, et al () studied the geographical hunting patterns of lone actor terrorists and found them to engage in spatial decision‐making similar to other criminals. Terrorist violence risk assessment, however, is not necessarily improved by the addition to an instrument of more and more variables arguably associated with such violence (Pressman & Flockton, ); a more parsimonious instrument, on the other hand, may be both scientifically reliable and more practically useful for counterterrorism efforts to prevent such acts of targeted violence.…”
Section: Discussionmentioning
confidence: 99%
“…Clarke and Newman () argued that terrorists will strike iconic targets , which is a function of their ideology motivating them to attack (see also Becker, ; Drake, ). Evidence indicates that terrorists, in fact, often favor iconic and/or symbolic targets (Gruenewald et al., ; Marchment, Bouhana, & Gill, ). As noted, however, more than 80% of mass shootings in the United States are unrelated to politics and are instead motivated by grievances versus specific persons, or by a quest for infamy (Capellan, ; Osborne & Capellan, ; Silva, ).…”
Section: Scp Terrorism and Preventing Or Reducing Public Mass Violencementioning
confidence: 99%
“…McGarrell, Freilich, and Chermak () suggested that an ILP approach to counterterrorism is relevant as, first, these events are rarely spontaneous and often involve a lengthy planning stage, and second, terrorism is often a local problem. In fact, Marchment, Bouhana, and Gill () demonstrated the distance‐decay effect in a sample of lone‐actor terrorists when examining the residence‐to‐attack journeys of this type of offender. Hence, the lone‐actor terrorist threat is theoretically detectable given the appropriate intelligence.…”
Section: Policy Implicationsmentioning
confidence: 99%